Credit Ratings and the Evolution of the Mortgage-Backed Securities Market - He, Jie; Qian, Jun; Strahan, Philip E (American Economic Review, 2011)
We compare the structure and performance of private (non-GSE) mortgage-backed securities sold by large issuers vs. those sold by small issuers over the period 2000–2006. Securities sold by large issuers have less subordination—a greater fraction of the deal receiving AAA rating—than those sold by small issuers. Prices for AAA-rated and non-AAA rated tranches sold by large issuers fell more when the market turned down than those sold by small issuers, and this difference was concentrated among tranches issued between 2004 and 2006. These results suggest that rating agencies grant favorable ratings to large issuers, especially during market booms.